The Effectiveness of Simulation and Role-Play in Teaching Speaking for Students with Different Levels of Motivation - Lutfi, Agus Adib; Sutopo, Djoko; Rukmini, Dwi (Universitas Negeri Semarang, 2018)
Simulation and role play as techniques of teaching have been studied and believed to be effective for teaching speaking. In speaking class, students’ interest and motivation were also improved as effect of the techniques.This study aimed at examining the effectiveness of simulation and role-play as techniques of teaching speaking to the students with different levels of motivation. The design of this research was quasi-experimental study with 2 X 2 factorial designs. The independent variables were simulation and role play technique while dependent variable was students’ speaking ability. The data were gathered through a test, questionnaire, observation, and informal interview with teachers and students. Then, I analyzed the result from questionnaire and speaking test using t-test and ANOVA.The results of this study showed that simulation technique to teach speaking to the students with high and low motivation (80.8 and 65) and role-play technique is (71.9 and 70.9). Mean score of simulation technique was higher than role-play technique and and the total mean of the students with high motivation was higher than the students with low motivation. However, both of techniques were effective to students with high and low motivation. The value of sig. of techniques and motivation was 0.00. It meant that sig.value was lower than 0.05. It indicated that there was significant difference between techniques and students’ motivation to teach speaking. In other words, speaking techniques were able to improve students’ speaking competence and those correlated directly with the level of students’ motivation.Based on the result of the study, it can be inferred that students were getting advantages of using simulation and role-play techniques to teach speaking. The students’ score was significantly increased. they were also indirectly motivated to speak English and they gradually forgot the negative feeling such as shyness and lack of confidence